(untitled) (Journal of Dhaka Medical College, 2025)
Background: Patients experiencing stroke with Left Ventricular Systolic Dysfunction (LVSD) face elevated mortality rates, heightened dependency, prolonged hospitalization, increased ICU referrals, and greater complication risks compared to those without LVSD. Objective: This study aims to evaluate the outcomes differences of ischemic stroke patients with and without LVSD, as well as within subgroups of LVSD severity. Materials and Methods: The study was Conducted in the Department of Neurology, Dhaka Medical College and Hospital (DMCH) from January 2022 to December 2023. In this prospective cohort study we enrolled 117 acute ischemic stroke patients meeting predetermined inclusion and exclusion criteria. LVSD diagnosis was established through echocardiography. Patient outcomes, including hospital duration, ICU necessity, mortality, and modified Ranking Scale (mRS) scores, were assessed and compared. Results: Among the 117 patients, 61 were classified under stroke with LVSD, while 56 were without LVSD. The mean(SD) age was 65.50(9.94) years for LVSD and 63.78(10.85) years for non-LVSD patients. Male predominance was observed in both groups, with 83.6% males in the LVSD group and 67.9% in the non-LVSD group. Mortality rates at hospital and the first month were 5.4 times higher in LVSD patients compared to non-LVSD patients (9.8% vs. 1.8%, p- value 0.029). Total 3-month mortality was nearly three times higher in LVSD patients (27.9% vs. 10.7%, p <0.05). mRS scores indicated significantly poorer functional outcomes at 1 and 3 months for LVSD patients compared to non-LVSD patients. (mRS >2 in 95.1% vs 83.9%) at 1 month and mRS >2 in 68.9% vs 39.3% at 3 months). Length of hospital stay was longer for LVSD patients (median [IQR] 10 [8-15] days) compared to non-LVSD patients (median [IQR] 7 [4-11] days). Need for ICU referral of the ischemic stroke patients with LVSD was 2.3 times more than non-LVSD patients (32.8% vs 14.3%, p- value 0.029). Conclusion: Ischemic Stroke patients with LVSD exhibit poorer clinical outcomes, higher mortality rates, increased dependency, prolonged hospital stay and greater need for ICU referral compared to those without LVSD. J Dhaka Med Coll. 2024; 33(1) : 32-41